Removal of Heavy Metal Ions Using the Fungus - Ridvan Say; Nalan Yilmaz; Adil Denizli (Adsorption Science & Technology)
The potential use of the fungus Penicillium canescens for the removal of cadmium, lead, mercury and arsenic ions from aqueous solutions was evaluated in this study. Equilibrium biosorption of the heavy metal ions was attained in 4 h. The binding of heavy metal ions to P. canescens was clearly pH-dependent. Under acidic conditions, the heavy metal ion loading capacity increased with increasing pH, presumably as a result of heavy metal speciation and competition with hydrogen ions for the same binding sites. The adsorption of heavy metal ions attained a plateau value at ca. pH 5.0. The maximum adsorption capacities of the heavy metal ions studied onto the fungal biomass under non-competitive conditions were 26.4 mg/g for As(III), 54.8 mg/g for Hg(II), 102.7 mg/g for Cd(II) and 213.2 mg/g for Pb(II), respectively. The competitive adsorption capacities of the heavy metal ions were 2.0 mg/g for As(III), 5.8 mg/g for Hg(II), 11.7 mg/g for Cd(II) and 32.1 mg/g for Pb(II), respectively, at a 50-mg/l initial concentration of the metal ions. The same affinity order was observed under non-competitive and competitive adsorption conditions, i.e. Pb(II) > Cd(II) > Hg(II) > As(III). The equilibrium loading capacity of Pb(II) was greater than that of other metal ions, the fungal biomass showing preference towards the binding of Pb(II) over Cd(II), Hg(II) and As(III). Elution of heavy metal ions was performed using 0.5 M HCl. The fungus Penicillium canescens could be used for biosorption over six cycles.